Protection of Victims of Digital Sexual Violence: A Comparative Study of Indonesia and South Korea - Sela, Mutiara Aprilia Putri; Fitri, Winda; Hutauruk, Rufinus Hotmaulana (Fakultas Syariah INSURI Ponorogo, 2026)
The development of digital technology has given rise to a new form of violence in the form of digital sexual violence, including deepfake pornoghraphy which has not been fully accommodated in the Indonesian legal system. This study aims to compare legal protection for victims of digital sexual violence in Indonesia and South Korea and to formulate strategies for strengthening regulations in Indonesia. The method used normative legal research, with a legislative, conceptual, case, and comparative approach, analyzing regulations and legal practices in both countries. The results show that Indonesia already has a legal basis through the TPKS Law, the ITE Law, and the Criminal Code, but does not yet specifically regulate forms of AI-Based DBV such as deepfake pornography. Implementation challenges include digital evidence, inter-agency coordination, and mechanisms for content removal. In contrast, South Korea has more responsive regulations, supported by specialized agencies focused on victim protection and recovery. The novelty of this research lies in its comparative analysis that focuses on institutional strengthening and technical mechanisms for handling digital sexual violence as concrete recommendations for legal reform in Indonesia.